PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA MEMBER HERBALIFE - Hakim, Moch. Lukman; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2023)
In all companies, human resource is the driver of other resources, while leadership and motivation have certain levels of influence on performance that represents the resource’s value. This research was conducted from March to July 2022 with the object of supervisor-level Herbalife members in Malang city during the 2021-2022 period. Using simple random sampling, 143 of them were selected as the respondents. Here multiple linear regression was used for data analysis, performed in SPSS Statistics 25.0. This study finds that leadership and motivation partially and simultaneously have positive and significant effects on the performance of sales force. Therefore, it can be concluded that increases in leadership and motivation lead to better performance among supervisor-level Herbalife members in Malang city. Hence, the uplines of supervisor members are expected to consider leadership and motivational aspects in order to improve members’ performance, especially those at supervisor level.